2015
DOI: 10.1111/rda.12615
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Whole Ovary Cryotreatments for Fertility Preservation

Abstract: The goal of this study was to compare a traditional slow-freeze method (TF) with an open unidirectional slow freeze cooling system (UF) for whole ovary cryopreservation. Therefore, whole pig ovaries were randomly assigned to (A) fresh control, (B) traditional slow freeze (TF) or (C) unidirectional slow freeze (UF). Ovaries were perfused with 10% DMSO in Krebs-Ringer. For TF, whole ovaries were placed in specimen jars containing 10% DMSO and placed into a specialized container for freezing filled with propan-2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…From the morphologocal comparison, our results revealed that freezing affects micro-environment of preantral and antral follicles in ovaries. Morphological damage of ovarian tissue from freezing has been reported by many previous studies of murine [20], bovine [11], pig [21], and human [22]. Consistent with the previous reports, the detachment between oocyte-granulosa complex and basal granulosa cell layer was found in our study.…”
Section: Discussionsupporting
confidence: 93%
“…From the morphologocal comparison, our results revealed that freezing affects micro-environment of preantral and antral follicles in ovaries. Morphological damage of ovarian tissue from freezing has been reported by many previous studies of murine [20], bovine [11], pig [21], and human [22]. Consistent with the previous reports, the detachment between oocyte-granulosa complex and basal granulosa cell layer was found in our study.…”
Section: Discussionsupporting
confidence: 93%
“…In mice, it has been shown that generation of live young is possible using oocytes derived from xenografted ovaries tissue (Snow et al, 2002). Although the efficiency is very limited in pigs, whole ovarian tissue or fragmented ovarian cortex were cryopreserved and xenografted in an immunodeficient nude mice (Kaneko et al, 2003;Kikuchi et al, 2006;Lotz et al, 2015;Gabriel et al, 2017). Another alternative approach for fertility preservation was the xenograft of the whole ovary into ovariectomized nude rats (Nichols-Burns et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Whole-organ cryopreservation would revolutionize the options available for organ donation and treatment of transplant recipients, as it would gain time to improve donor–recipient matching and therefore reduce the numbers of transplant rejections, as well as the intensity of the immunosuppression required [ 9 ]. Despite partial successes have been achieved with the kidney [ 10 ], heart [ 9 ], uterus [ 11 – 14 ], and ovary [ 15 , 16 ] in animal models, using perfusion-based equilibration protocols for CPAs as previously reviewed [ 17 ], the current freezing techniques do not ensure the survival and function of organs and they are far from being ready for routine clinical applications [ 18 ]. Most of the perfusion-based protocols for organ cryopreservation that have been published share the common feature that the CPA equilibration durations used range from approximately 25 minutes up to a couple of hours.…”
Section: Discussionmentioning
confidence: 99%